(untitled) (Sains Humanika, 2013)
Soft skills are important in virtually every profession in the workplace. Therefore, when evaluating employees, organizations will look for graduates with soft skills in addition to technical skills. However, in-depth studies on the extent these skills have been acquired by students in local higher education institutions have not been fully explored. Thus, this paper discusses this issue based on a study on 165 studentsâ€™ soft skills assessment forms completed by industry supervisors during 2011 industrial training. Data was analyzed descriptively and inferentially using t-test. Findings of this study found that generally, teamwork skills, professionalism, social responsibility, and ICT skills were generally at high level. However, communication and problem solving skills were found to be at a moderate level. The study also found that skills in using ICT hardware, accept criticism, respect for others’ views, and time management skills were effective differentiators in explaining genders differences. The research has brought meaningful implications for undergraduate students, employers and policy makers.